Work Character Readiness of Vocational High School Students Post Covid-19 Outbreak - Ranti Meizatri; Rifma Rifma (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
Work character is a critical issue for vocational high school students in addition to their knowledge and competencies. This study described the level of work character readiness of vocational high school students' during the Covid-19 outbreak. The subjects of this study were third-grade vocational high school students in five vocational high schools at Padang City in the spectrum: (1) fisheries and marine, (2) business and management, (3) performing arts, (4) tourism, and (5) information and communication technology. Respondents were 75 students consisting of 40 females, and 35 males were selected using the proportional stratified random sampling technique. Instrument development refers to two indicators, namely moral character and work character. The instrument was validated by experts and through validity and reliability testing. The results testing showed that validity and reliability with the respective rho count 0.927> rho table 0.648 and r results in 0.907> r table 0.514. Data analysis used simple statistics to determine the respondent's level of achievement level (RAL) from the readiness of male and female students' moral and work characteristics. The results showed that the achievement level of job readiness of vocational high school students in Padang city had reached 85.5%. The result of this study has inference that the distance learning system (online learning) during the Covid-19 pandemic did not harm the readiness of the work character of vocational high school students.┬á